Efficacy of surgeon-directed suprascapular and axillary nerve blocks in shoulder arthroscopy: a 3-arm prospective randomized controlled trial - Pamela Boekel, MBBS (Hons), MSc; Sarah G. Brereton, MBBS, MTrauma; Kenji Doma, PhD, BSpExcSci (Hons); Andrea Grant, BSpSci; Alex Kippin, MBBS, MPHTM; Matthew Wilkinson, MBBS; Levi Morse, BPhty (Hons), BMBS (Hons) (JSES International, 2023)
Background: The use of regional anesthesia in shoulder arthroscopy improves perioperative pain control, thereby reducing the need for opioids and their recognized side effects. Occasionally one type of block is not suitable for a patient’s anatomy or comorbidities or requires a specially trained anesthetist to safely perform. The primary aim of this study is to compare the efficacy of 3 different nerve blocks for pain management in patients undergoing shoulder arthroscopy. Methods: A 3-arm, blinded, randomized controlled trial in patients undergoing elective, unilateral shoulder arthroscopic procedures between August 2018 and November 2020 was conducted at a single center. One hundred and thirty participants were randomized into 1 of 3 regional anesthesia techniques. The first group received an ultrasound-guided interscalene block performed by an anesthetist (US + ISB). The second group received an ultrasound-guided suprascapular nerve block and an axillary nerve block by an anesthetist (US + SSANB). The final group received a suprascapular nerve block without ultrasound and an axillary nerve block under arthroscopic guidance by an orthopedic surgeon (A + SSANB). Intraoperative pain response, analgesia requirements, and side effects were recorded. Visual analogue pain scores and opioid doses were recorded in the Post Anaesthesia Care Unit (PACU) and daily for 8 days following the procedure. Results: Twelve patients withdrew from the study after randomization, leaving 39 participants in US + ISB, 40 in US + SSANB, and 39 in A + SSANB. The US + ISB group required significantly lower intraoperative opioid doses than US + SSANB and A + SSANB (P < .001) and postoperatively in PACU (P < .001). After discharge from hospital, there were no differences between all groups in daily analgesia requirements (P = .063). There was significantly more nerve complications with 6 patient-reported complications in the US + ISB group (P = .02). There were no reported differences in satisfaction rates between groups (P = .41); however, the A + SSANB group was more likely to report a wish to not have a regional anesthetic again (P = .04). Conclusion: The US + ISB group required lower opioid doses perioperatively; however, there was no difference between groups after discharge from PACU. The analgesia requirements between the US + SSANB and A + SSANB were similar intraoperatively and postoperatively. A surgeon-administered SSANB may be a viable alternative when an experienced regional anesthetist is not available.